Treatment of DIHS/DRESS syndrome with combined N-acetylcysteine, prednisone and valganciclovir – a hypothesis - Moling, Oswald (International Scientific Literature, Inc., 2012)
BACKGROUND: Drug-induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms (DIHS/DRESS) is a rare and severe adverse drug reaction with an associated mortality of 10–20%. Clinical worsening despite discontinuation of the culprit drug is considered a characteristic feature of DIHS/DRESS. Besides the early recognition of the syndrome and discontinuation of its causative drug, the mainstay of treatment is systemic corticosteroids. Nevertheless, treatment of severe DIHS/DRESS is not well defined, as corticosteroids may sometimes not be effective, and decreasing the dose may be associated with flaring of the disease. CASE REPORT: A 38-year-old woman with high fever, malaise, abdominal pain, rash, and elevated liver enzymes received immediate high-dose N-acetylcysteine, because acetaminophen hepatotoxicity was suspected. N-acetylcysteine administration was associated with a significant clinical improvement. However, within the next week DIHS/DRESS syndrome was diagnosed, which explained all the symptoms, and which was subsequently treated with prednisone and valganciclovir. CONCLUSIONS: New options necessary to improve treatment of severe DIHD/DRESS have to consider its sequential pathogenetic mechanisms. N-acetylcysteine might neutralize the drug-derived reactive metabolites, which are responsible for protein adduct formation and specific T cell stimulation, and replete the glutathione stores that counterbalance oxidative stress. Prednisone might inhibit lymphoproliferation and valganciclovir might prevent complications related to HHV-6 reactivation. We therefore propose the unprecedented combination of N-acetylcysteine, prednisone and valganciclovir as a treatment option for DIHS/DRESS.